UPAYA MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM (PAI) MENGGUNAKAN METODE HYPNOTEACHING BAGI SISWA KELAS VII C SMPN 1 LIMBANGAN KABUPATEN KENDAL TAHUN 2016/2017 - As’ari, Kasan (Universitas Islam Sultan Agung, 2018)
This study aims to find out what should be done to improve the learning outcomes of Islamic Teaching subject matters (PAI) by using hypnoteaching method for students of grade VII C of State Junior High School 1 Limbangan Kendal in 2016/2017 ineven semester.This research is a classroom action research that aims to improve the learning result of PAI in the classroom. The subject of the study were students of class VII C who had the lowest learning result.This research was conducted in three cycles. Each cycle used a model or research design Kemmis and Taggart which is consisting of four components namely planning, acting, observing, and reflecting. Data completion technique used test learning result technique, where there are two tests result of learning. Those are pre-test and post-test. The test in this research used formative test in the form of objective test, the test question manifested in multiple-choice form. Data analysis technique by comparing average result of learning test before and after action is done.The results of this research showed that hypnoteaching method can improve PAI learning result with indicators, there is enhancement on the average PAI learning result from pre-test by 70.06 increased to 73.91 in cycle I, increased again to 76.79 in cycle II and increased again to 78.94 in cycle III. KKM achievement also increased from precycles of 36.36% to 60.61% incycle I, increased again to 72.73% incycle II and increased again to 81.82% during cycle III. From the result, there has been a significant improvement in the result of cycle III, so hypnoteaching method can be standardized into a model to improve the results of learning PAI with the following actions: 1. Affirmation by saying yells that involved the body movement and emotion, 2. Visualization by presenting something in the shadow alongside the members' body movement, 3. Reciprocation by peer tutoring in a group, 4. Invitation the students to be grateful for the knowledge Allah has given.